Analisis Social Return On Investment (SROI) Pada Program Entrepreneurship Workshop - Arman Arman; Tri Siwi Agustina (Journal of Economic, Bussines and Accounting (COSTING), 2024)
Social Return on Investment (SROI) is a technique to measure the impact/benefit of a project or program. This study aims to analyze the impact of social investment from the implementation of the program, Entrepreneurship Workshop "Glinds Act - Global Minds, Local Impact: Transforming Education & Entrepreneurs". In this research, the type of data used is primary data. The analysis procedure used is the SROI analysis method using a stakeholder-focused approach, viewed from three aspects: economic, social, and environmental. The results showed that every Rp1 (one rupiah) invested in the Entrepreneurship Workshop "Glinds Act - Global Minds, Local Impact: Transforming Education & Entrepreneurs" will generate a social return of Rp. 38, 52 (thirty - eight point fifty - two rupiah). This ratio is quite high and promises a high return as well. Keywords: Social Return on Investment, CSV